TTHE INFLUENCE OF VILLAGE OFFICIAL COMPETENCE ON THE IMPLEMENTATION OF VILLAGE FINANCIAL ACCOUNTING STANDARDS (SAKD): A CONTINGENCY STUDY IN POKA VILLAGE - Rita J D Atarwaman; Yosefa.Reresi; Inkana Dewanti Banea; Permata Sary Lausiry (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Transparent and accountable village financial management is one of the important indicators in realizing good village governance. The government has established the Village Financial Accounting Standards (SAKD) as guidelines for the preparation and presentation of village financial reports. However, in practice, the implementation of SAKD still faces various challenges, particularly those related to the competence of village officials as financial managers. This study aims to analyze the effect of village officials’ competence on the implementation of the Village Financial Accounting Standards (SAKD) in Poka Village. This study uses a quantitative approach with a survey method. Data were collected through the distribution of questionnaires to all village officials directly involved in village financial management using a saturated sampling technique. The independent variable in this study is the competence of village officials, which includes technical, managerial, and conceptual competencies, while the dependent variable is the implementation of SAKD. Data were analyzed using linear regression analysis with the assistance of statistical software. The results of the study indicate that the competence of village officials has a positive and significant effect on the implementation of SAKD in Poka Village. These findings suggest that improving the competence of village officials can encourage more optimal implementation of SAKD and enhance the quality of village financial management and reporting in a sustainable manner, thereby supporting public transparency and accountability as well as more effective and responsible village financial decision-making by the village government and stakeholders.